ANALISIS TINDAKAN PENGHINDARAN PAJAK PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA DALAM PERSPEKTIF EKONOMI ISLAM - CHAZANATUL ILMI; DINI SABRINA; WINDA AFRIYENIS (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2017)
The theme of the article is the banks and financial institutions. This study aims to determine how much the level of tax evasion by state-owned companies and know the correlation of tax evasion with the opinion of the scholars in Islam. This research belongs to Mixed research. The population in this study are all state-owned companies listed on the BEI in 2013 until 2015. While the sample of this study is determined by purposive sampling method so that obtained 13 sample companies. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is descriptive analysis. The results obtained based on data processing. Of the 13 (thirteen) companies that become the sample of SOE companies listed on the BEI in the period 2013-2105 there are 5 (five) companies that conduct tax evasion. Three of them have political connections, but have no connection in the Islamic economic system. All tax evasion actions by the company are directly derived from the thoughts and judgments of the competent authorities in the company, and not on the opinions of Islamic scholars.